Cardiology in the Pandemic COVID-19: What is the Impact in Clinical Activity? A Cardiologia na Pandemia COVID-19: Que Impacto na Atividade Clínica? - Oliveira, Mário; Sousa, Paulino; Sousa, Lídia; Mendes, Cláudia; Labucha, Marta; Macedo, Filipe (Gazeta Médica, 2020)
The COVID-19 Pandemic involved changes in the organization of the health care system, with interruption of the clinical programmed activity during the lockdown period, which, associated with the fear of contamination, had important repercussions in medical care. In this article, we analyzed data from the cardiology centers of CUF Infante Santo and CUF Porto hospitals during the state of national emergency. These hospitals, with similar characteristics in cardiovascular multifunctionality and integrated in the centers for treatment of COVID-19, had a reduction of more than 70% of face-to-face consultations, surpassing 60% for almost all diagnostic tests, compared to the same period of 2019. This was even more pronounced when looking for the evolution during the first four months of 2020. Elective invasive procedures were also reduced, with a marked fall in April. However, urgent interventions due to acute coronary syndromes remained unchanged compared to the same period in 2019. The need to inform the population regarding the importance of using hospital emergencies and the maintenance of safety recommendations is reinforced, and the growing role of telemedicine and home-based care is addressed, as well as the reorganization of the hospital teams to improve the multidisciplinary dynamicity in Cardiology.